Inhaling Singing, a New Extended Vocal Technique - Vanhecke, Françoise; Leman, Marc 1958-; Raes, Godfried-Willem 1952-; Universiteit Gent (Ghent, Belgium) Faculty of Arts and Philosophy Department of Art, music and theatre sciences (2017)
The second half of the 20th and the 21st Century delivers music with liberty for use of the voice, which allows the use of “Inhaling” singing. Vocal sounds or even words can be produced while a singer is inhaling. This can create a strained or even humorous effect that has been mostly linked to folk, ethnic and rock music. During recent research on that inhaling technique, we discovered that there are several ways of interpreting and perceiving such sounds. To improve the technique, improvisation and sound painting are ways to discoverthat sound idiom. Inhaling singing requires confidence and knowledge of the vocal instrument as well as experience from the performer. Timbre modulation of the voice, using amplitude of in-breathing are performed with support of body movement. Inspiration and phonation are performed at the same time.The acoustic analysis of the fundamental frequency produced while inhaling singing reveals that the sound we hear is not always what we expect we should see. The impact of supraglottis with arytenoide cartellages is correlated with the sopraglottis vibrators, the physiological cause. The vocal folds give various states of thickness and thinness and the intrinsic muscles are very active.The acoustic analysis was performed using datasets from both male and female voices. For the measurement and analysis we used spectrograms and an electroglottogram (EGG) from the Voce Vista software developed by Don Miller. A video-stroboscopyand a nasofibroscopy are performed by connecting a camera in parallel with the audio data acquisition. A series of kymogramms show us that several co-vibrators are active. The study is practice based on: inhaling production of a single sustained freely chosen sound, inhaling glissando, inhaling singing on double tones, multiphonics, electronic sounds at different ranges of pitch and melody (tonal and atonal) using vibrato and non vibrato and dynamics on which the singer feels comfortable. Experimenting and exploring this Inhaling Singing on my own voice, I discovered more and more flexibility in the way of performing. With that new way of singing I manage now to sing a defined melody. The tessitura for the IS is until now situated in the high range of the female voice. Using that new kind of singing enables to switch immediately to other styles of singing. Thus we can gain an insight in the optimum use of vowels required for reproduction. We found that quite some music scores and their vocal notations are not really well defined. Scores and works by Tzvi Avni, Joan La Barbara, Irma Bilbao, Meyer Kupferman, Dieter Schnebel have been examined as well as 'Aria' by John Cage. We also attempted to do specific notational proposals in our own compositional work. Pathological and therapeutics aspects can be useful for clinical cases.(Taken from http://www.inhalingsinging.be)
Thesis submitted for the degree of Doctor of Arts: Music (22/06/2017, Ghent)
Keywords: Singing; Extended technique; Artistic research